Le privilège de dénoncer: justice pour toutes les victimes de violences sexuelles - Souffrant, Kharoll-Ann; Diallo, Rokhaya (Les éditions du remue-ménage, 2022)
''Le privilège de dénoncer cherche à savoir pourquoi les femmes et les filles noires sont largement absentes du débat public lorsqu'il est question de violences sexuelles. Kharoll-Ann Souffrant explore sans détour les raisons historiques de ce constat à partir d'exemples tirés du Québec, de la France et des États-Unis. Entre les impacts actuels de la colonisation et de l'esclavage, les stéréotypes liés à la sexualité des Noir·es ainsi que les failles du système de justice criminelle, l'autrice assemble les pièces du casse-tête pour révéler les dynamiques à l'œuvre derrière la marginalisation des femmes afrodescendantes. La parole des survivantes noires serait-elle doublement invisibilisée, tant par les institutions patriarcales que par un certain féminisme blanc et libéral qui aurait accaparé le mouvement #MeToo? Une invitation à élargir sans délai notre compréhension des violences sexuelles et racistes, et ce, pour le bénéfice de l'ensemble de la société. «Dans un Québec qui – comme tant de sociétés – s'élance encore d'un pas hésitant lorsqu'il s'agit de confronter le racisme systémique, la parole de Kharoll-Ann Souffrant est précieuse. Elle est une femme noire dont les racines se trouvent sur la terre où s'est érigée la première république noire au monde, à Haïti, née d'une révolution victorieuse contre la France coloniale, contre l'oppression esclavagiste. Aujourd'hui Kharoll-Ann Souffrant pose sa plume telle la digne héritière de celles et ceux qui se sont dressé·es il y a plus de deux cents ans. Avec verve, elle décrypte ce racisme conçu pour écraser ses aïeux, dont les résidus persistent à obstruer les regards qui se posent sur elle.» ''– Site de l'éditeur.
Keywords: 2000 à aujourd'hui; 2020-2029; afro-féminisme; amériques; approches et analyses; canada; cours; discipline; féminisme afroaméricain; haïti; histoire et politique; intersectionnalité; inégalités; patriarcat; point de vue situé; pol4212; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; travail social; témoignage; violences; violences sexistes et sexuelles; violences sexuelles

Work in the Intersections: A Black Feminist Disability Framework - Bailey, Moya; Mobley, Izetta Autumn (Gender & Society, 2019)
A Black feminist disability framework allows for methodological considerations of the intersectional nature of oppression. Our work in this article is twofold: to acknowledge the need to consider disability in Black Studies and race in Disability Studies, and to forward an intersectional framework that considers race, gender, and disability to address the gaps in both Black Studies and Disability Studies. By employing a Black feminist disability framework, scholars of African American and Black Studies, Women’s, Gender, and Sexuality Studies, and Disability Studies have a flexible and useful methodology through which to consider the historical, social, cultural, political, and economic reverberations of disability.
Keywords: EDI; afro-féminisme; approches et analyses; capacitisme; care; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; philosophie; premier cycle; racisme; ressource en ligne; santé; sciences humaines; sex1920; sexisme; systèmes d'oppressions; thématiques; études critiques du handicap; études de genres

African Canadian leadership: Continuity, transition, and transformation - Kitossa, Tamari; Lawson, Erica; Howard, Philip S. S. (University of Toronto Press, 2019)
Challenging the myth of African Canadian leadership "in crisis," this book opens a broad vista of inquiry into the many and dynamic ways leadership practices occur in Black Canadian communities. Exploring topics including Black women’s contributions to African Canadian communities, the Black Lives Matter movement, Black LGBTQ, HIV/AIDS advocacy, motherhood and grieving, mentoring, and anti-racism, contributors appraise the complex history and contemporary reality of blackness and leadership in Canada. With Canada as a complex site of Black diasporas, contributors offer an account of multiple forms of leadership and suggest that through surveillance and disruption, practices of self-determined Black leadership are incompatible with, and threatening to, White "structures" of power in Canada. As a whole, African Canadian Leadership offers perspectives that are complex, non-aligned, and in critical conversation about class, gender, sexuality, and the politics of African Canadian communities.
Keywords: afro-féminisme; amériques; approches et analyses; canada; cours; discours dominant; fem3300; féminisme afroaméricain; histoire et politique; identités LGBTQIA2+; maternité; militance; premier cycle; racisme; régions géographiques; systèmes d'oppressions; thématiques

Ce qui se passe quand les blanc.he.s changent - hooks, bell (Rencontres radicales : pour des dialogues féministes décoloniaux, 2018)
Postface de Nassira Hedjerassi
Keywords: 2000 à aujourd'hui; afro-féminisme; amériques; approches et analyses; cours; discours dominant; fem3400; féminisme afroaméricain; féminisme décolonial; histoire et politique; militance; premier cycle; privilèges; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Vers une pédagogie du conflit - hooks, bell (Rencontres radicales : pour des dialogues féministes décoloniaux, 2018)
Postface de Nassira Hedjerassi
Keywords: afro-féminisme; amériques; approches et analyses; cours; fem3100; fem3400; féminisme afroaméricain; féminisme décolonial; histoire et politique; militance; premier cycle; régions géographiques; thématiques; états-unis

Contre misogynoir. Des Caribéennes francophones entre black feminism et afroféminisme - Melyon-Reinette, Stéphanie (https://www.archipelies.org:443, 2018)
Misogynoir : un terme qui résume parfaitement la réalité sociale et identitaire des femmes noires aux États-Unis, comme en France hexagonale : il désigne tous les manifestations et comportements discriminatoires à l’égard des femmes noires et de couleur basés tout à la fois sur le sexisme, le racisme ou le colorisme. Si cette terminologie est récente, le phénomène est aussi ancien que le monde binaire (blanc vs noir) dont il procède : le système plantationnaire et ses avatars. Par ailleurs, on ne peut négliger les aspects intersectionnels de la période-même avec les classes phénotypico-sociales. Dans cet article, nous interrogerons la place et le positionnement des Caribéennes francophones dans le cadre des mouvements féministes de Paris. Ainsi, prendrons-nous en compte la pluriethnicité des communautés féminines noires de France et les liens qu’elles tissent avec ces différentes aires d’implantation : Région parisienne, Caraïbe et Amérique noire.
ISSN: 2777-5909 Publisher: CRILLASH (Centre de recherches interdisciplinaires en lettres, langues, arts et sciences humaines)/Presses de l’Université des Antilles
Keywords: afro-féminisme; approches et analyses; cours; fem3300; féminisme afroaméricain; féminisme décolonial; histoire et politique; premier cycle; racisme; ressource en ligne; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Se défendre : une philosophie de la violence - Dorlin, Elsa (Zones, 2017)
"En 1685, le Code noir défendait " aux esclaves de porter aucunes armes offensives ni de gros bâtons " sous peine de fouet. Au xixe siècle, en Algérie, l'État colonial français interdisait les armes aux indigènes, tout en accordant aux colons le droit de s'armer. Aujourd'hui, certaines vies comptent si peu que l'on peut tirer dans le dos d'un adolescent tout en prétendant qu'il était agressif, armé et menaçant. Une ligne de partage oppose historiquement les corps " dignes d'être défendus " et ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce " désarmement " organisé des subalternes et des opprimés au profit d'une minorité jouissant d'un droit permanent à porter des armes et à en user impunément pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Du jiu-jitsu des suffragettes aux pratiques insurrectionnelles du ghetto de Varsovie, des fusils des Black Panthers aux patrouilles queer, Elsa Dorlin retrace une généalogie philosophique de l'autodéfense politique. Derrière l'histoire officielle de la légitime défense, il est ici question du récit des " éthiques martiales de soi ", ces histoires ensevelies où le Sujet ne préexiste pas à sa propre défense, où le fait de se défendre en attaquant apparaît à la fois comme la condition de possibilité d'un soi et la matière des mythologies politiques. Cette histoire - une histoire de la violence - conditionne la définition même de la subjectivité moderne. Elle s'écrit à la lumière d'une relecture critique de l'histoire de la philosophie politique, où Hobbes et Locke sont à confronter avec Franz Fanon, Michel Foucault ou Judith Butler."–Page 1 et 4 de la couverture.
Keywords: afro-féminisme; approches et analyses; cours; discipline; fem3100; féminisme afroaméricain; féminisme décolonial; féminismes noirs; histoire et politique; mouvements sociaux; philosophie; premier cycle; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Où allons-nous, maintenant ? - Hill Collins, Patricia (Les cahiers du CEDREF. Centre d’enseignement, d’études et de recherches pour les études féministes, 2017)
L’idéal de liberté a longtemps été un aspect central de l’identité nationale américaine. C’est une vision attrayante : libération des persécutions religieuses, entre autres ; liberté qui promet de traiter tant les riches que les pauvres comme des citoyen.n.e.s devant la loi ; et liberté de viser aussi haut que peut vous emmener votre désir. La démocratie constitue un mécanisme pour atteindre cet idéal de liberté, un processus de construction de la capacité d'une communauté à atteindre ces buts.
Keywords: afro-féminisme; amériques; approches et analyses; cours; fem3100; féminisme afroaméricain; histoire et politique; intersectionnalité; premier cycle; ressource en ligne; régions géographiques; thématiques; états-unis

Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

Kimberlé Crenshaw: The urgency of intersectionality | TED Talk - Crenshaw, Kimberlé (TedTalk, 2016)
Now more than ever, it's important to look boldly at the reality of race and gender bias – and understand how the two can combine to create even more harm. Kimberlé Crenshaw uses the term "intersectionality" to describe this phenomenon; as she says, if you're standing in the path of multiple forms of exclusion, you're likely to get hit by both. In this moving talk, she calls on us to bear witness to this reality and speak up for victims of prejudice.
Keywords: activisme; afro-féminisme; approches et analyses; com5170; cours; discipline; droit; droits civiques; droits des femmes*; droits humains; féminisme afroaméricain; histoire et politique; intersectionnalité; justice sociale; militance; premier cycle; science politique et droit; thématiques

Life notations of Daisy Sweeney: Reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.
http://hdl.handle.net/10315/31697
Keywords: 1900-1999; DIG; afro-féminisme; amériques; approches et analyses; discipline; femmes* noires; histoire et politique; maternité; montréal; musique; mémoires/thèses; philosophie; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail

Representing the Black female subject in western art - Nelson, Charmaine (Routledge, 2010)
Nelson analyzes not only how, where, why and by whom black female subjects have been represented in Western art, but also what the social and cultural impacts of the colonial legacy of racialized Western representation have been. She poses questions about the concepts of production, the consequences of comsumption and more
Disponible en ligne: https://doi-org.proxy.bibliotheques.uqam.ca/10.4324/9780203851241 Contenu: Through an-other's eyes : white Canadian artists – Black female subjects – Racing childhood : representations of black girls in Canadian art – Slavery, portraiture, and the colonial limits of Canadian art history – The fruits of resistance : reading portrait of a Negro slave on the sly – Tying the knot : Black female slave dress in Canada – Coloured nude : fetishization, disguise, dichotomy – The "hottentot venus" in Canada : modernism, censorship, and the racial limits of female sexuality – White marble, Black bodies, and the fear of the invisible Negro : – Signifying blackness in mid-nineteenth-century neoclassical sculpture – Vénus Africaine : race, beauty, and African-ness – Allegory, race, and the four continents : Jean-Baptiste Carpeaux's les quatre parties du monde soutenant la sphere céleste – Conclusion : whiteness as collective narcissism, towards a new vision.
Keywords: afro-féminisme; approches et analyses; arts; cours; discipline; féminisme afroaméricain; har4610; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; système colonial; systèmes d'oppressions; thématiques

Déclaration du Combahee River Collective - Combahee River Collective (Black Feminism : anthologie du féminisme africain-américain 1975-2000, 2008)
« Les textes présentés dans ce recueil du Black feminism - le premier en France - explorent sur une période de trente ans les thèmes de l'identité, de l'expérience singulière, de la sororité, de la sexualité, comme la place dans les institutions, les coalitions nécessaires et les alliances possibles, les formes culturelles de rébellion et de lutte, le passage de témoin entre générations. Pourquoi, en France, ex-puissance coloniale, l'équivalent d'un féminisme noir n'a-t-il pas existé? Ces textes, par leur vitalité et leur perspicacité politiques, invitent à poser cette question et à s'interroger autrement sur les faux-semblants de l'universalisme républicain comme sur les points aveugles du féminisme français. »– Quatrième de couverture.
Première publication: 1977 Donné en lecture au cours POL4212.
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; cours; cycles supérieurs; fem1000; fem3300; fem9000; féminisme africain; féminisme afroaméricain; féminismes noirs; histoire et politique; incontournable; intersectionnalité; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; thématiques; états-unis

Antiesclavagisme et féminisme. Le combat théologique des sœurs Grimké aux États-Unis dans les années 1830 - Grandjean, Michel (Études théologiques et religieuses, 2008)
Sarah et Angelina Grimké, actives militantes de la lutte contre l’esclavage, jouèrent également un rôle important au sein du féminisme naissant. Michel Grandjean* montre que les arguments bibliques et théologiques qui leur permettent de défendre les droits du Noir face au Blanc servent ainsi à promouvoir la femme. Dans ses Lettres sur l’égalité des sexes (1838), Sarah Grimké condamne avec une cinglante ironie les traditions masculines et se livre en particulier à une exégèse libre et nouvelle d’un certain nombre de péricopes sur les relations entre l’homme et la femme.
https://www.cairn.info/revue-etudes-theologiques-et-religieuses-2008-3-page-317.htm
Keywords: 1800-1899; afro-féminisme; amériques; antiesclavagisme; approches et analyses; cours; discipline; fem1000; féminisme afroaméricain; histoire et politique; mouvements féministes; mouvements sociaux; premier cycle; périodes historiques; ressource en ligne; régions géographiques; science des religions; sciences humaines; thématiques; états-unis

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

Le patriarcat ou le féminisme noir - Charlery, Hélène (Revue française d’études américaines, 2007)
Les travaux actuels parus sur le féminisme et la population noire aux États-Unis insistent fréquemment sur l’attitude des Africaines-Américaines à l’égard de l’idéologie féministe (Terrelonge ; Roth). Peu d’études en revanche ont été consacrées aux prises de position des hommes et des dirigeants noirs sur la question. D’après les analyses récentes, une majorité d’Africains-Américains, hommes et femmes, redouterait que le féminisme ne divise les genres au sein du groupe, qu’il n’écarte les Noirs de leur priorité dans la lutte contre la discrimination raciale ou encore qu’il n’engendre un débat médiatique sur la sexualité des Africains-Américains. À ces raisons, Pauline Terrelonge ajoute l’héritage du nationalisme noir de la seconde moitié des années 1960 (Terrelonge 563). On constate aussitôt que les prises de positions citées précédemment sont liées à l’histoire des Noirs aux États-Unis et de leur stigmatisation dans les discours dominants. Pour les Africains-Américains, le féminisme imposerait alors une confrontation entre la race et le genre, bien que les féministes noires aient toujours envisagé de prendre en compte « l’intersectionalité » des deux notions .
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; intersectionnalité; masculinité; patriarcat; pol5185; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; états-unis

The master’s tools will never dismantle the master’s house - Lorde, Audre (Sister outsider: essays and speeches, 2007)
Première édition: 1984
Keywords: afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; fem3600; féminisme afroaméricain; histoire et politique; lesbianisme; militance; premier cycle; régions géographiques; thématiques; émotions; états-unis; études littéraires

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis